Stochastic geometry analysis of electromagnetic field exposure in coexisting sub-6 GHz and millimeter wave networks - Seman, Norhudah; Anwar Apandi, Nur Ilyana; Elijah, Olakunle; Han, Chua Tien; Li, Yonghui (Institute Of Electrical And Electronics Engineers Inc., 2021)
The deployment of sub-6 GHz macro-cell networks, which are overlaid by millimeter-wave (MMW) small-cells, is a promising method to accommodate the unprecedented growth of data traffic demands and user devices. Although such a hybrid network could provide seamless connectivity and achieve high-quality services, there is a need to ensure that the growing number of base stations (BSs) does not affect biological safety, especially when the BSs are operated at high frequencies. This paper focuses on an analytical framework to investigate the electromagnetic field (EMF) exposure in a cellular network with coexisting sub-6 GHz and MMW BSs using a stochastic geometry approach. Locations of sub-6 GHz and MMW BSs are modeled as Poisson point processes (PPP). By incorporating different channel propagation, antenna, and fading models for sub-6 GHz and MMW tiers, the incident power density (IPD) coverage probability and the average IPD are derived and validated by Monte Carlo simulations. The impact of various system parameters such as BS density, number of antenna elements, and blockage density are investigated to gain insights on the network scenario. The results demonstrate that the variation of the EMF exposure level closely depends on the BS density and the number of antennas deployed at the BS. The results also show that the receiver sensitivity has a significant impact on the average IPD. For the same receiver sensitivity, it is revealed that an MMW user is exposed to a higher average IPD level than the sub-6 GHz counterpart. The results are also compared with the existing international regulations.